2016
DOI: 10.1016/j.progsurf.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption structures and energetics of molecules on metal surfaces: Bridging experiment and theory

Abstract: Adsorption geometry and stability of organic molecules on surfaces are key parameters that determine the observable properties and functions of hybrid inorganic/organic systems (HIOSs). Despite many recent advances in precise experimental characterization and improvements in rst-principles electronic structure methods, reliable databases of structures and energetics for large adsorbed molecules are largely amiss. In this review, we present such a database for a range of molecules adsorbed on metal single-cryst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
159
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(170 citation statements)
references
References 257 publications
10
159
0
1
Order By: Relevance
“…The same behavior was recently observed for benzene/Ag(111) 36 ; in this case, the adsorption energy obtained with HSE+MBD was in better agreement with experimental results than that obtained with the PBE+MBD method. In our case, for anthracene/Ag(111), the adsorption energy obtained using the HSE+MBD method (E ads =−1.18 eV) is still within range of the experimental values reported for other oligoacenes, such as benzene, naphthalene and pentacene, adsorbed on the Ag(111) surface (0.68-1.5 eV) 9,[36][37][38] .…”
Section: 02åsupporting
confidence: 87%
“…The same behavior was recently observed for benzene/Ag(111) 36 ; in this case, the adsorption energy obtained with HSE+MBD was in better agreement with experimental results than that obtained with the PBE+MBD method. In our case, for anthracene/Ag(111), the adsorption energy obtained using the HSE+MBD method (E ads =−1.18 eV) is still within range of the experimental values reported for other oligoacenes, such as benzene, naphthalene and pentacene, adsorbed on the Ag(111) surface (0.68-1.5 eV) 9,[36][37][38] .…”
Section: 02åsupporting
confidence: 87%
“…). Following Woodruff, we designate this distance as “XSW (coherent) position,” d A , noting that “vertical (molecular) adsorption height,” “surface molecule distance,” “bonding distance” and “perpendicular height” are used synonymously in the literature. d A is calculated as dnormalA=(znormalAzAgn)(n1)Δzbulk, where znormalAzAgn represents the distance between atom A and the plane of the lowest Ag‐layer in the cluster, n is the number of Ag‐layers in the cluster and Δzbulk is the distance between vertical Ag layers as obtained from the periodic slab‐supercell calculations (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Several interesting studies of metal‐organic interfaces are found in the literature, where the interactions of a variety of organic π ‐systems, such as pentacene, perylene derivatives or phthalocyanines, have been studied on the low index planes of noble metals, namely Ag, Cu and Au . In this paper, we will restrict the discussion to the adsorption of Perylene‐3,4,9,10‐tetracarboxylic dianhydride (PTCDA) on the Ag(110) surface which is a prototype system as its adsorption characteristics have been studied extensively . Combined LEED‐ARPES (Low Energy Electron Diffraction; Angle‐Resolved Photoelectron Spectroscopy), and NIXSW (Normal Incidence X‐Ray Standing Waves) studies of the PTCDA/Ag(110) system provide detailed information about the orientation of the molecule on the substrate and the adsorption heights of respective atoms.…”
Section: Introductionmentioning
confidence: 99%
“…8 and 9). Typically, molecules on metal surfaces, [10][11][12][13][14][15][16][17][18] three-and twodimensional solids, [19][20][21][22] and molecular complexes 23,24 a) Electronic mail: alozano@bcamath.org have become the workhorse paradigm for examining the impact of vdW forces on the binding of weakly interacting systems. A general outcome from these investigations is that the inclusion of vdW forces to GGA functionals often results in improved binding energies and adsorption distances that are in better agreement with available experimental data.…”
mentioning
confidence: 99%